Oxidation Enhances Binding of Extrahelical 5-Methyl-Cytosines by Thymine DNA Glycosylase - Beierlein, Frank; Volkenandt, Senta; Imhof, Petra (Journal of Physical Chemistry B, 2022)
The DNA repair protein thymine DNA glycosylase (TDG) removes mispaired or damaged bases, such as oxidized methyl-cytosine, from DNA by cleavage of the glycosidic bond between the sugar and the target base flipped into the enzyme’s active site. The enzyme is active against formyl-cytosine and carboxyl-cytosine, whereas the lower oxidized hydroxymethyl-cytosine and methyl-cytosine itself are not processed by the enzyme. Molecular dynamics simulations with thermodynamic integration of TDG complexed to DNA carrying one of four different (oxidized) methyl-cytosine bases in extrahelcial conformation, methyl-cytosine (mC), hydroxymethyl-cytosine (hmC), formyl-cytosine (fC), or carboxyl-cytosine (caC), show a more favorable binding affinity of the higher oxidized forms, fC and caC, than the nonsubstrate bases hmC and mC. Despite rather comparable, reaction-competent conformations of the flipped bases in the active site of the enzyme, more and stronger interactions with active site residues account for the preferred binding of the higher oxidized bases. Binding of the negatively charged caC and the neutral fC are strengthened by interactions with positively charged His151. Our calculated proton affinities find this protonation state of His151 the preferred one in the presence of caC and conceivable in the presence of fC as well as increasing the binding affinity toward the two bases. Discrimination of the substrate bases is further achieved by the backbone of Tyr152 that forms a strong hydrogen bond to the carboxyl and formyl oxygen atoms of caC and fC, respectively, a contact that is completely lacking in mC and much weaker in hmC. Overall, our computational results indicate that the enzyme discriminates the different oxidation forms of methyl-cytosine already at the formation of the extrahelical complexes.<br